Firearm Availability, Homicide, and the Context of Structural Disadvantage - Semenza, Daniel C. (Homicide studies, 2023)
This study examines how legal and illegal firearm availability correspond to subsequent rates of firearm and non-firearm homicide in 226 U.S. cities from 2010 through 2017. We also assess how city-level economic disadvantage conditions this relationship. Results show that greater availability of illegal guns corresponds to future rates of firearm homicide while the rate of legal firearms dealers does not significantly influence firearm homicide. The association between firearm availability and homicide is conditional upon level of structural economic disadvantage. Our findings support efforts to decrease access to illegal firearms to reduce gun violence, especially among vulnerable and disadvantaged communities.